A genetic strategy generating wheat with very high amylose content. Issue 9 (3rd February 2015) - Regina, Ahmed; Berbezy, Pierre; Kosar‐Hashemi, Behjat; Li, Suzhi; Cmiel, Mark; Larroque, Oscar; Bird, Anthony R.; Swain, Steve M.; Cavanagh, Colin; Jobling, Stephen A.; Li, Zhongyi; Morell, Matthew
Summary: Resistant starch (RS), a type of dietary fibre, plays an important role in human health; however, the content of RS in most modern processed starchy foods is low. Cereal starch, when structurally manipulated through a modified starch biosynthetic pathway to greatly increase the amylose content, could be an important food source of RS. Transgenic studies have previously revealed the requirement of simultaneous down‐regulation of two starch branching enzyme (SBE) II isoforms both located on the long arm of chromosome 2, namely SBEIIa and SBEIIb, to elevate the amylose content in wheat from ~25% to ~75%. The current study revealed close proximity of genes encoding SBEIIa and SBEIIb isoforms in wheat with a genetic distance of 0.5 cM on chromosome 2B. A series of deletion and single nucleotide polymorphism (SNP) loss of function alleles in SBEIIa, SBEIIb or both was isolated from two different wheat populations. A breeding strategy to combine deletions and SNPs generated wheat genotypes with altered expression levels of SBEIIa and SBEIIb, elevating the amylose content to an unprecedented ~85%, with a marked concomitant increase in RS content. Biochemical assays were used to confirm the complete absence in the grain of expression of SBEIIa from all three genomes in combination with the absence of SBEIIb from one of the genomes.